Perbandingan Kinerja Keuangan Antara Bank Konvensional dengan Syariah yang Terdaftar di Bursa Efek Indonesia pada Tahun 2020-2023 - Dwi Kharisma Wati; Civi Erikawati (Pajak dan Manajemen Keuangan, 2024)
Background: The emergence of Islamic banks will definitely increase competition in the banking market. Many factors influence banking growth in Indonesia. The current condition has two main threats that must be considered because they can show the weakness of global banking: the weakening of the commercial property market and the connection of banks with non-bank financial institutions. Method: This study uses descriptive statistics, normality test, and independent sample T test. Results: Conventional and sharia banks do not have significant differences in financial performance, according to the Return On Assets (ROA), Capital Adequacy Ratio (CAR) indicators. On the other hand, the Return On Equity (ROE), Loan to Deposit Ratio (LDR), and Operating Costs Operating Income (BOPO) indicators show that there is no significant difference in financial performance between conventional and sharia banks. Conclusion: Islamic banks show better performance than conventional banks in terms of Return On Assets (ROA), Capital Adequacy Ratio (CAR) and BOPO. These ratio values ​​have higher values. However, conventional banks show better performance in Return On Equity (ROE) and Loan to deposit ratio (LDR) with better average ROE and LDR values.